2009
DOI: 10.1111/j.1600-0501.2009.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized‐controlled clinical trial of customized zirconia and titanium implant abutments for single‐tooth implants in canine and posterior regions: 3‐year results

Abstract: Objectives: The aim was to test whether or not zirconia abutments exhibit the same survival and technical/biological outcome as titanium abutments. Material and methods: Twenty‐two patients receiving 40 single‐tooth implants in canine and posterior regions were included. The implant sites were randomly assigned to 20 zirconia and 20 titanium abutments. All‐ceramic and metal–ceramic crowns were fabricated. At baseline, 6, 12 and 36 months, the reconstructions were examined for technical and biological problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
223
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(262 citation statements)
references
References 22 publications
(28 reference statements)
16
223
2
11
Order By: Relevance
“…The line of the crown margin can be adjusted to the line of the soft tissue, and the requirement for an anatomic emergence profile and controllable cement gap in a single implant-supported restoration can be met individually. [4][5][6] Because of the biocompatibility and minor color change in the peri-implant mucosa, CAD/CAM abutments made of zirconia are used increasingly in the aesthetically important anterior region. 7,8 In addition to the different possibilities for connecting the implant and abutment, it is possible to use prefabricated stock-or individually milled CAD/CAM zirconia abutments, both of which today are available in one-and two-piece designs.…”
Section: Introductionmentioning
confidence: 99%
“…The line of the crown margin can be adjusted to the line of the soft tissue, and the requirement for an anatomic emergence profile and controllable cement gap in a single implant-supported restoration can be met individually. [4][5][6] Because of the biocompatibility and minor color change in the peri-implant mucosa, CAD/CAM abutments made of zirconia are used increasingly in the aesthetically important anterior region. 7,8 In addition to the different possibilities for connecting the implant and abutment, it is possible to use prefabricated stock-or individually milled CAD/CAM zirconia abutments, both of which today are available in one-and two-piece designs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this lack of RCTs could be attributed to the narrow scope of the review, since RCTs were found comparing other types of implant abutments. Baldini et al (23) ; Cosgarea et al (24) ; Carrillo de Albornoz et al (25) ; Ferrari et al (26), (27) ; Sailer et al (28) ; Zembic et al (29), (30) , compared different types of titanium abutments versus zirconia; while others compared between the different types of zirconia abutments: Büchi et al (31) and Thoma et al (32) compared the veneered zirconia versus white zirconia; Paolantoni et al (33) compared one-piece versus two-piece custom made zirconia anchorages and final prosthetic restoration; and Schepke et al (34) reported the comparison between stock versus customized zirconia.…”
Section: Summary Of Main Results:-mentioning
confidence: 99%
“…Ancak titanyum abutmentlar renginden dolayı özellikle ince 24 tarafından ise yitriyum stabilize zirkonyumdan kişisel abutment üretilmiştir. Zirkonyum abutmentların alü-mina abutmentlara göre daha üstün sonuçlar verdiğini gösteren klinik ve laboratuar çalışmaları [24][25][26][27][28] olmakla beraber benzer sonuçlara sahip olduğunu gösteren bir çalışmada bulunmaktadır 29 .…”
Section: Döküm Kişisel Abutmentlarunclassified